Long-term survival with multiple metastasectomies for pulmonary osteosarcoma: a case report - Satoshi Takamori; Hiroyuki Oizumi; Jun Suzuki; Katsuyuki Suzuki (Surgical Case Reports, 2021)
Abstract Background Repeat pulmonary metastasectomy (PM) considerably improves the prognosis of patients with pulmonary metastases of osteosarcoma. Reports have demonstrated a significantly improved prognosis in patients who have undergone repeat metastasectomy for osteosarcoma; however, there have been no reports with more than six metastasectomies. Herein, we describe the long-term survival of a patient following resection of multiple tumors and other treatments for metastatic osteosarcoma. Case presentation A 28-year-old woman underwent extensive resection and postoperative adjuvant chemotherapy for right tibial sarcoma. Over the years, she developed repeated pulmonary metastases. First, 116 metastases were removed from the bilateral lungs. After that, multiple PMs of approximately 250 tumors and other treatments for deep metastatic lesions were performed. The patient died of the underlying disease 24 years after the primary surgery. Conclusions This case report demonstrates the long-term survival benefit of a multidisciplinary treatment centered on multiple metastasectomies.